The Identification of Animals that Have the Potential as Seed Dispersers in the West Lampung Biodiversity Park : Identifikasi satwa yang berpotensi sebagai penyebar biji di Taman Keanekaragaman Hayati, Lampung Barat - Putri, Desma Ramadhina; Kanedi, Mohammad; Priyambodo, Priyambodo; Agustrina, Rochmah (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2023)
West Lampung Biodiversity Park is a biodiversity conservation area established in 2015. The purpose of establishing a biodiversity park is to provide a reserve area, both in-situ and/or ex-situ, for local biological resources, especially plants whose structure and composition can support the existence and sustainability of animal diversity. One group of animals that has an important role in the sustainability of flora biodiversity is seed disperser. This research was conducted to find out the current biodiversity status of animals having potential as seed dispersers. The research was carried out in September–November 2021 using interview and observation methods. The data was analyzed descriptively. The results show that in the West Lampung Biodiversity Park, 10 types of animals have the potential to spread seeds, consisting of 4 members of the aves class and 6 members of the mammal class. There are 4 types of fruit spread by Aves and 17 types of seeds spread by Mammals